Persepsi Guru Pendidikan Anak Usia Dini Dalam Menyusun Modul Ajar Kurikulum Merdeka - St. Maria Ulfah; Nur Afiah (Journal on Education, 2024)
This study aims to examine the views of PAUD teachers on the Independent Curriculum. This study uses a descriptive qualitative approach with a case study type, and the analysis method used is the Miles & Huberman technique. The total population in this study consists of 24 PAUD teachers. Data was collected through questionnaires and interviews. The results of this study show that the view of PAUD teachers about the Independent Curriculum is that the Independent Curriculum is easier to implement than the previous curriculum, because it is adapted to the needs of students in urban and rural areas, and reduces the administrative burden of teachers which is often time-consuming. The Independent Curriculum has the potential to improve the quality of education in Indonesia, but its success depends heavily on proper training and good understanding by teachers.